Christian Neoplatonism Nicholas of Cusa and Giovanni Pico della Mirandola: the point of intersection - Михайлова, І.І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article deals with the formation of the metaphysical foundations of the Renaissance.